2007
DOI: 10.1021/ja076885x
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Oxygen Exchange between the [HxNb6O19]8-x(aq) Lindqvist Ion and Aqueous Solutions [J. Am. Chem. Soc. 2006, 128, 14712−14720].

Abstract: Page 13107, Figure 3. The reported isotope effect 18 k bridge for hydrolysis of the monoanion of mNBP is in error; the correct value is 1.0157 ( 0.0009. For comparison, 18 k bridge for pNPP monoanion hydrolysis is 1.0087. Since the maximum 18 k bridge for the alkyl leaving group mNBP is expected to be about twice 1 that for the aryl leaving group in pNPP, the KIEs for the two monoanion reactions are similar in proportion to their respective upper limits. This indicates a similar extent of P-O bond fission in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…80 In other cases, positions can be proposed based on 17 O NMR spectra. 25,[80][81][82][83][84] Computationally, this subject has been 50 tackled by many authors. [85][86][87][88][89] To analyze the effect of protonation on 17 O NMR of POMs, we focus on the well characterized decavanadate [V 10 O 28 ] 6anion, represented in Figure 7, since it features seven structural oxygen sites, six of which are external and could potentially be protonated.…”
Section: Effects Of Localised and Mobile Protons On The Chemical Shiftmentioning
confidence: 99%
“…80 In other cases, positions can be proposed based on 17 O NMR spectra. 25,[80][81][82][83][84] Computationally, this subject has been 50 tackled by many authors. [85][86][87][88][89] To analyze the effect of protonation on 17 O NMR of POMs, we focus on the well characterized decavanadate [V 10 O 28 ] 6anion, represented in Figure 7, since it features seven structural oxygen sites, six of which are external and could potentially be protonated.…”
Section: Effects Of Localised and Mobile Protons On The Chemical Shiftmentioning
confidence: 99%
“…This is demonstrated by using six hexaniobate, [Nb 6 O 19 ] 8– , cluster anions to encapsulate mixed-valent cobalt oxide cores comprising 13 Co atoms which, arising from partial occupancies at specific positions, closely match the mixed-valent structures of cubic-spinel and monoclinic Co 3 O 4 . The complex, 1 , was then used in place of bulk cobalt oxide as a cocatalyst for the direct Z-scheme reduction of CO 2 by solar light and water.…”
Section: Introductionmentioning
confidence: 99%
“…Of the wealth of POM catalysts that have been synthesized over decades, Group-V POMs with Lindqvist ion structure, particularly Nb 6 O 19 8– , are ideal candidates to act as base hydrolysis catalysts due to the high charge density of the exposed oxygen atoms . It is therefore not surprising that alkali salts of the Nb 6 O 19 8– ion have recently been reported to hydrolyze nerve agents. , Computational work on Nb 6 O 19 8– has included structural studies using DFT methods, the proposal (also with DFT methods) of an open-cage intermediate that leads to oxygen exchange with solvent measured with NMR, and a recent molecular dynamics study of the protonation of Nb 6 O 19 8– in aqueous media . However, no mechanistic studies of the base hydrolysis reactions with Nb 6 O 19 8– have been reported yet.…”
Section: Introductionmentioning
confidence: 99%